Pengaruh Career Adaptability dan Aging Experience pada Late Career Planning yang Dimediasi oleh Occupational Future Time Perspective - Choirun Nisa (Jurnal Indonesia Sosial Teknologi, 2022)
Globally, the elderly population continues to increase, in Indonesia it is predicted to increase higher than the elderly population in other Asian regions. The condition of the aging population can also have a negative impact if the increase in the number of elderly people is not balanced with proper preparation for old age, resulting in the elderly being far from healthy, active, and productive, which of course will increase the burden on the productive age population on the elderly population. This study aims to help determine why and how older workers plan their careers after retirement by examining the effects of career adaptation and aging experience as contributing factors to OFTP-mediated late career planning. This study used 50 respondents with an age range of 50-70 years who live in Sooko District. We found that career adaptability has a significant effect on the formation of late career planning, and aging experience which is divided into 4 dimensions, namely physical loss, personal growth, and social loss, has no significant effect on OFTP and late career planning, but gaining self-knowledge has a significant effect.. The managerial implication in this study is that the company or related organization can review the supporting factors in career adaptation and aging experience, especially to gain self-knowledge, because it has a considerable influence on workers' views on career planning continuation.